2007
DOI: 10.1007/s00401-006-0186-1
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA alterations in primary (de novo) and secondary glioblastomas

Abstract: We assessed alterations in the EGFR/PTEN/PI3K pathway in 107 primary (de novo) glioblastomas and 32 secondary glioblastomas that progressed from low-grade or anaplastic astrocytomas. SSCP followed by DNA sequencing in exons 9 and 20 of the PIK3CA gene revealed missense mutations in 5/107 (5%) primary and 1/32 (3%) secondary glioblastomas. Quantitative real-time PCR showed PIK3CA amplification (>3 copy numbers) in 14/107 (13%) primary and 3/32 (9%) secondary glioblastomas. Only one glioblastoma showed both PIK3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 39 publications
3
67
0
6
Order By: Relevance
“…PI3K regulates the single transmission of AKT phosphorylation. (Gallia et al, 2006, Kita et al, 2007 Several studies show that PI3K inhibition sensitizes glioma cells to radiation and chemical therapy (Opel et al, 2008;Prevo et al, 2008). Modulation of AKT signalling cascade using miRNAs in glioblastoma cell lines was described also in Nan et al In this study, transfection of miR-451 mimicked reduced expression levels of Akt1, Cyclin D1, MMP-2, MMP-9 and Bcl-2.…”
Section: Discussionsupporting
confidence: 60%
“…PI3K regulates the single transmission of AKT phosphorylation. (Gallia et al, 2006, Kita et al, 2007 Several studies show that PI3K inhibition sensitizes glioma cells to radiation and chemical therapy (Opel et al, 2008;Prevo et al, 2008). Modulation of AKT signalling cascade using miRNAs in glioblastoma cell lines was described also in Nan et al In this study, transfection of miR-451 mimicked reduced expression levels of Akt1, Cyclin D1, MMP-2, MMP-9 and Bcl-2.…”
Section: Discussionsupporting
confidence: 60%
“…Elevated AKT phosphorylation has been observed in up to 85% of glioblastoma cell lines and patient samples (Wang et al 2004). RTK-independent activation of this pathway in glioblastoma can occur via mutation or amplification of PIK3CA (p110a) (Gallia et al 2006;Kita et al 2007; The Cancer Genome Atlas Research Network 2008), and PIK3CD (p110d) is also overexpressed in some gliomas (Mizoguchi et al 2004). Moreover, the TCGA study revealed recurrent mutations in the gene encoding the p85a regulatory subunit PIK3R1, which likely drive PIK3CA activation through decreased SH2 domain-mediated inhibition (Sun et al 2010).…”
Section: Pi3k Pathwaymentioning
confidence: 99%
“…Elevated AKT phosphorylation has been observed in up to 85% of glioblastoma cell lines and patient samples [45]. RTK-independent activation of this pathway in glioblastoma can occur via mutation or amplification of PIK3CA (p110a) [46,47], and PIK3CD (p110d) is also overexpressed in some gliomas [48]. Other amplified regions containing oncogenes, for example AKT3 [22,49] and CCND2 [22,27].…”
Section: Amplificationmentioning
confidence: 99%
“…Mutations in PIK3CA and PIK3R1, coding for the PI3K catalytic subunit p110a and regulatory subunit P85a, have been described [22,23]. RTK-independent activation of this pathway in glioblastoma can occur via mutation of PIK3CA (p110a) [46,47] or through recurrent mutations in the gene encoding the p85a regulatory subunit PIK3R1. This will likely drive PIK3CA activation through decreased SH2 domain-mediated inhibition [87].…”
Section: Mutationsmentioning
confidence: 99%